PROGRAM PENDEWASAAN USIA PERKAWINAN UNTUK MENCEGAH TERJADINYA PERNIKAHAN DINI PADA REMAJA : Literature Review - Berthalia Veronica Aprilyani (2020)
Early marriage to adolescents is defined as an event carried out by children who are married under age ie under the age of 20 years for women and 25 years for men, many of the effects caused if early marriage is most dangerous, namely death to mothers who give birth when underage age. This literature review aims to analyze the methods or media used to provide education and information on marriage age maturity programs to prevent early marriage to adolescents. Literature Review is done by searching for articles using an electronic database that is with Google Scholar. There are various methods and media that can be used, among others: health education counseling, psychoeducation, interventions of religious and traditional leaders, communication of information and education, providing information with media such as audiovisuals, booklets and leaflets, snakes and ladders and snowball throwing, group guidance with peers, counseling socialization, and youth information communication programs (PIK-R). Suggestions for further reviewers can be done to find out which actions are most effective in preventing early marriage in adolescents.